Efeito da fração diclorometano de Sideroxylon obtusifolium T. D. Penn sobre o biofilme de espécies de Candida - Costa, Bruna Palmeira (2020)
Researchers have been working in the search for substances that have antifungal activity and can be used in the treatment of oral candidiasis. Sideroxylon obtusifolium (S. obtusifolium) is a plant found mainly in caatinga of Brazilian Northeastern and has been popularly used in the treatment of several conditions. Its antimicrobial activity has been described in the literature, but in a scarce way. The aim of this study was to analyze the phytochemical profile of the dichloromethane fraction (DICF) of the leaves of Sideroxylon obtusifolium T. D. Penn hydroethanolic extract as well as to evaluate its antifungal and antibiofilm activity on species of the genus Candida spp. After the production of the extract and subsequent fractionation, the analysis of the DICF phytochemical profile was carried out through qualitative and quantitative screening beyond 1H nuclear magnetic resonance. Then, the antifungal activity of the DICF was investigated by determining the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) on Candida albicans and non-albicans species. After that, it was analyzed the effect of the fraction on the growth kinetics (Time-Kill Curve) of C. albicans (ATCC 10232) and adherence and mature biofilm inhibition of C. albicans (ATCC 10232), C. glabrata (ATCC 90030) and the association between the two yeasts based on the number of colony forming units (CFU) and metabolic activity. The data from the analysis of the DICF's action on the growth kinetics of C. albicans and the antibiofilm efficacy were analyzed using the Statistical Package for the Social Sciences (SPSS) program with a significance level of 5%. The one-way test of variance (one-way ANOVA) and Tukey's post-test were used to check differences in the dependent variables between the groups respectively. Phytochemical characterization suggested the majority of saponins and phenolic compounds. The DICF showed MIC values between 250 µg/mL and 1000 µg/mL and MFC between 1000 µg/mL and > 1000 µg/mL, with fungistatic activity on most of the studied fungal species. The fraction concentration of 2000 μg/mL showed fungicidal activity for a period of 24 h on C. albicans, showing greater activity on reducing the adhesion and biofilm of this fungal species. The fraction concentration of 1000 μg/mL was effective on reducing the adhesion and biofilm of C. glabrata (ATCC 90030), while on the biofilm of the association of the two strains this value dropped to 250 μg/mL. The DICF showed antifungal activity, being fungistatic against most of the tested species. In addition, it reduced the adherence and biofilm of Candida spp. In view of these results, it is necessary to carry out further analyzes such as antioxidant activity and toxicity tests with the DICF, aiming at a possible clinical use of the fraction as an alternative antifungal therapy in dentistry.